Improvement of Composite Beam with Web Opening Using Posttensioning Tendons under Static and Cyclic Loadings - Utino Worabo Woju; Eyob Tadesse Dadebo (Advances in Civil Engineering)
In practice, the passage of service utilities through web opening causes a significant load-carrying capacity loss and introduces a change of failure mode of the composite beam. This study aims to improve the load-carrying capacity and stiffness of open-web composite beams subjected to static and cyclic loading using posttensioning tendons. To achieve the desired objective, 18 mechanical models have been developed using ABAQUS by considering the shape and location of the web opening, span/depth ratio, and degree of connection as study parameters. The finite element analysis result was validated with experimental results from relevant literature. Results indicate that the external posttensioning tendons increase load-carrying capacity to 25.05% for rectangular and 20.61% for circular web opening under static loadings. Under cyclic loading, the improvement is 9.24% for rectangular while 2.50% reduction in deflection has been observed for circular web opening. As a span-to-depth ratio increased as 11.54, 15.38, and 23.08, the load-carrying capacity improved by 26.35%, 20.67%, and 8.65%, respectively, for static loadings. Likewise, 2.03%, 1.24%, and 4.95% improvement were observed under cyclic loadings, respectively. Furthermore, compared to one row of 16 mm shear stud provision, the load-carrying capacity increased by 30.67% for connection in two rows under cyclic loading.